Study of the genus Cephennium Müler & Kunze, 1822 (Coleoptera, Staphylinidae, Scydmaeninae) from the Balkan Peninsula. Part II. New species of the subgenus Cephennium s. str. - Stevanović, Miroslav (Zootaxa, 2014)
Twelve new species of the genus Cephennium Müler & Kunze, 1822 are described: C. (s. str.) irenae sp. n. (from Serbia, Bosnia and Herzegovina, and Montenegro); C. (s. str.) sladjanae sp. n. and C. (s. str.) fallax sp. n. (both from Serbia and Bulgaria); C. (s. str.) viti sp. n. (from Serbia, Macedonia, Greece and Bulgaria); C. (s. str.) fairchildi sp. n., C. (s. str.) ivanjicense sp. n., C. (s. str.) serbicum sp. n. and C. (s. str.) remisianum sp. n. (all from Serbia); C. (s. str.) assingi sp. n. and C. (s. str.) angelinii sp. n. (both from Greece); C. (s. str.) mlejneki sp. n. (from Montenegro) and C. (s. str.) vitoshae sp. n. (from Bulgaria). Aedeagi and male protibiae of all species are illustrated. Cephennium (s. str.) bosnicum Ganglbauer, 1899 is redescribed and its lectotype is designated.